An investigation to determine the normal 1st to 5th metatarsal peak pressure and PTI ratio of the forefoot. (December 2022) - Rajan, R.A.; Kerr, M.; Evans, H.; Ananda-Rajan, DR
Abstract: Background: The foot support has been described as that of a tripod. Biomechanical studies often report on peak pressures and pressure time integrals under specific areas of the foot. Reference needs to be made to the normal tripod distribution especially in the forefoot. In the forefoot the ratio between the 1st metatarsal and the 5th metatarsal on the medial and lateral columns of the foot respectively provide an excellent reference especially if the normal ratio is known. This study provides conclusive evidence of the 1st to 5th metatarsal ratio for peak pressures and pressure time integrals in the normal foot to be used as a reference. Methods: A group of normal healthy volunteers (n = 12) and a group of patients with unilateral end stage hallux rigidus (n = 17) were recruited. Repeated measures of 1st and 5th metatarsal peak pressures and Pressure time integrals were measured to determine reliability of measurement and to provide a reference normal ratio. Results: In the healthy volunteer group, the 1st/5th metatarsal ratio for PTI was very close to 1 while it was just over 1.5 for peak pressure. In patients with unilateral end stage hallux rigidus, in the normal foot the 1st/5th metatarsal ratio for PP and PTI was very close to 1. These ratios were reproduced in the operated foot following 1st MTPJ replacement. Conclusion: This study using normal healthy volunteers and patients undergoing 1st MTPJ replacement has demonstrated that the normal 1st/5th metatarsal peak pressure and pressure time integrals should be close to 1.